Mammals of China - Smith, Andrew T., 1946-; Xie, Yan, 1967- (Princeton pocket guides., 2013)
China's breathtaking diversity of natural habitats--from mountains and deserts to grasslands and lush tropical forests--is home to more than 10 percent of the world's mammal species. This one-of-a-kind pocket guide describes the characteristics, geographic distribution, natural history, and conservation status of all 558 species of mammals found in China. An up-to-date distribution map accompanies each species account, and beautiful color illustrations by wildlife artist Federico Gemma depict a majority of the species. The definitive text is written by leading specialists and follows the mo.